2021
DOI: 10.3390/ijms22031176
|View full text |Cite
|
Sign up to set email alerts
|

Measurements Methods for the Development of MicroRNA-Based Tests for Cancer Diagnosis

Abstract: Studies investigating microRNAs as potential biomarkers for cancer, immune-related diseases, or cardiac pathogenic diseases, among others, have exponentially increased in the last years. In particular, altered expression of specific miRNAs correlates with the occurrence of several diseases, making these molecules potential molecular tools for non-invasive diagnosis, prognosis, and response to therapy. Nonetheless, microRNAs are not in clinical use yet, due to inconsistencies in the literature regarding the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 159 publications
(195 reference statements)
0
49
0
Order By: Relevance
“…RT-qPCR was employed for miRNA analysis in this study, since it shows excellent sensitivity, specificity, and reproducibility, requires only widely available standard equipment, and is thus more suitable for routine use than NGS [ 30 ]. Relative miRNA quantification methods are most commonly applied when using RT-qPCR [ 46 ]. The two normalization methods used in this study demonstrated overall good agreement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RT-qPCR was employed for miRNA analysis in this study, since it shows excellent sensitivity, specificity, and reproducibility, requires only widely available standard equipment, and is thus more suitable for routine use than NGS [ 30 ]. Relative miRNA quantification methods are most commonly applied when using RT-qPCR [ 46 ]. The two normalization methods used in this study demonstrated overall good agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding data normalization, the choice of appropriate reference genes is of particular importance in order to avoid bias in miRNA quantification. There is, however, neither a universally valid endogenous control nor a consensus on the most appropriate references miRNAs in biofluids [ 46 , 47 ]. We based our choice on miRNA expression data from the exploratory NGS study, which perfectly reflected the nature of the samples included in the current validation study [ 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs have been involved in many cancers and neurodegenerative diseases, such as multiple sclerosis, Parkinson's disease, and Alzheimer's disease [ 37 , 38 ]. Overall, miRNAs play an essential part in the occurrence and development of diseases [ 39 ].…”
Section: Mirnamentioning
confidence: 99%